The Theoretical Model of Assessment of Community Needs in Social Services - Борисова, А. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted the theheoretical model for assessing community needs for social services wich based on a combination of quantitative and qualitative methods of sociological research. The profession of social work should focusing on the identification of community needs and the development of resources to social services. Needs can be identified as the gap between what is determined as a necessary level of resources and what resources actually exist. The ability to examine needs in a systematic way through a needs assessment helps in the identification of what resources are lacking and provides a basis for developing the resources to meet those needs. The K. Neuber defines a needs assessment as "...a systematic process of data collection and analysis as inputs into resource allocation with a view to discovering and identifying goods and services the community is lacking in relation to the generally accepted standards and for which there exists some consensus as to the community's responsibility for their provision". But if we talk about needs in social work, we should remember Sopko R.I. and her work "Typology of Client Needs in Social Work" where she identifies four types of client needs in social work: a) Regulatory need, b) Need felt, c) Need expressed, d) Relative (comparative) need. The proposed theheoretical model for assessing community needs for social services has 3 stages: 1) researching of the expressed need – analysis of statistical data on the social structure of the population of the community and existing providers of social services; 2) researching of relative need – analysis of the quality of social services provided in the community; 3) result of needs assessment – analysis of the ratio of the level of satisfaction of expressed and relative needs.

Запропоновано теоретичну модель оцінки потреб громади в соціальних послугах, яка базується на поєднанні кі- лькісних та якісних методах соціологічних досліджень. Визначення існуючих надавачів соціальних послуг та соціаль- ної структури населення розкриває потреби в соціальних послугах, які надаються найбільш чисельним соціальним групам ОТГ. Проведення фокус-групи з метою дослідження потреби, яку визначають для себе жителі громади, дозво- лить сформувати комплексне бачення результатів оцінки потреб громади в соціальних послугах.
Теоретична модель оцінки потреб громади в соціальних послугах
Keywords: об'єднана територіальна громада; потреби клієнтів соціальної роботи; виражена потреба; віднос- на потреба; соціальна послуга; соціальний паспорт громади; метод фокус-групи.; united territorial community; social work client’s needs; expressed need; relative need; social service; community social passport; focus group method.